Tissue plasminogen activator in central nervous system physiology and pathology - Melchor, Jerry P.; Strickland, Sidney (Thrombosis and Haemostasis, 2005)
Although conventionally associated with fibrin clot degradation, recent work has uncovered new functions for the tissue plasminogen activator (tPA)/plasminogen cascade in central nervous system physiology and pathology. This extracellular proteolytic cascade has been shown to have roles in learning and memory, stress, neuronal degeneration, addiction and Alzheimer’s disease. The current review considers the different ways tPA functions in the brain.
Keywords: Tissue-type plasminogen activator; plasminogen; central nervous system; LTP; excitotoxicity